2014
DOI: 10.2514/1.b34986
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Instabilities in Gaseous Detonations: Comparison of Euler, Navier–Stokes, and Large-Eddy Simulation

Abstract: A large-eddy simulation is conducted to investigate the transient structure of an unstable detonation wave in two dimensions and the evolution of intrinsic hydrodynamic instabilities. The dependency of the detonation structure on the grid resolution is investigated, and the structures obtained by large-eddy simulation are compared with the predictions from solving the Euler and Navier-Stokes equations directly. The results indicate that to predict irregular detonation structures in agreement with experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 58 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…Due to the high resolution and low dissipation of the hybrid scheme, diffusion effect in viscous detonations should be dominated by the physical viscosity, while numerical dissipation in inviscid detonations can be almost entirely avoided. It has been reported that the diffusion effect mainly occurs at shear layers and unburned mixture boundaries [22]. The comparison between viscous and inviscid detonations showed that the growth of secondary instabilities (KH instability type) is suppressed in NS simulations [31,32].…”
Section: Viscosity Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to the high resolution and low dissipation of the hybrid scheme, diffusion effect in viscous detonations should be dominated by the physical viscosity, while numerical dissipation in inviscid detonations can be almost entirely avoided. It has been reported that the diffusion effect mainly occurs at shear layers and unburned mixture boundaries [22]. The comparison between viscous and inviscid detonations showed that the growth of secondary instabilities (KH instability type) is suppressed in NS simulations [31,32].…”
Section: Viscosity Effectsmentioning
confidence: 94%
“…In Fig.6(c), four secondary triple points coexist simultaneously thus generating more shear layers behind the triple points that undergo KH instability. Previous numerical and experimental investigations showed that in unstable detonations RM instability is the main mechanism for the generation of turbulent structures behind the detonation front [21], which indicated that the role of KH instability seems to be less important than that of the RM instability [22].…”
Section: Detonation Propagation After the Shutdown Of Hot Jetmentioning
confidence: 99%
“…[63,64] showed that from the comparison of detonations solved both by Euler and Navier-Stokes equations, diffusion effect has no crucial role in the overall structure of regular detonations due to the negligible effect of hydrodynamic instabilities. Therefore, the results obtained in this paper using Euler equations for regular detonations are nevertheless expected to give at least qualitatively correct conclusions.…”
Section: Numerical Schemementioning
confidence: 99%
“…Previously Oran et al (Oran et al, 1998) Mahmoudi et al, 2013;Mahmoudi et al, 2014) showed that from the comparison between Euler and NS equations, diffusion effect has no role in regular detonations, due to the absence of hydrodynamic Therefore, the conclusions obtained in this paper using the inviscid Euler equations for regular detonations are nevertheless expected to give at least qualitatively correct descriptions of detonation features.…”
Section: Methodsmentioning
confidence: 83%